Early Markers of Tubulointerstitial Fibrosis in Children With Idiopathic Nephrotic Syndrome: Preliminary Report. Issue 42 (October 2015) - Bieniaś, Beata; Zajączkowska, Małgorzata; Borzęcka, Halina; Sikora, Przemysław; Wieczorkiewicz-Płaza, Anna; Wilczyńska, Barbara
Abstract : Abstract: Tubulointerstitial fibrosis and tubular atrophy play a crucial role in the pathogenesis of chronic kidney disease (CKD). They are also major determinants in chronic kidney disease development and progression in patients with primary renal diseases characterized by persistent or recurrent proteinuria. The purpose of the study was to assess urinary excretion of alpha-glutathione S-transferase (alpha-GST), pi-glutathione S-transferase (pi-GST), neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), and serum NGAL level in children with idiopathic nephrotic syndrome (INS). Patients and methods: the study group comprised of 39 children with INS and the control group consisted of 20 healthy children. A total of 23 patients were affected with steroid-dependent nephrotic syndrome (SDNS) and 16 with steroid-resistant nephrotic syndrome (SRNS). In the majority of patients, a histopathologic examination revealed minimal change disease (MCD)—25 (64%). Focal segmental glomerulosclerosis (FSGS), mesangioproliferative glomerulonephritis (MesPGN), membranoproliferative glomerulonephritis (MPGN), and membranous glomerulonephritis (MGN) were diagnosed in 4 (10.3 %), 6 (15.5%), 2 (5.1%), and 2 (5.1%) children, respectively. Urinary alpha-GST, urinary pi-GST, urinary KIM-1, and urinary and serum NGAL concentrations were measured using specific enzyme-linked immunosorbent assay. The urinary results were expressed in nanograms per milligram of creatinine (ng/mg). Results: The authors observed significantly higher levels of urinary alpha-GST/creatinine ratio ( P  = 0.03), urinary KIM-1/creatinine ratio ( P  < 0.02), serum NGAL level ( P  < 0.01), and urinary NGAL/creatinine ratio ( P  = 0.02) in children with INS compared with controls. The median values of urinary pi-GST/creatinine ratio in children with INS and controls did not differ significantly. In children with SRNS, the median values of urinary NGAL/creatinine ratio ( P  = 0.02) and urinary KIM-1/creatinine ratio ( P  = 0.02) were significantly higher compared with children with SDNS. The authors noted significant positive correlation between KIM-1/creatinine ratio and proteinuria ( r  = 0.56, P  < 0.05). The analysis of alpha-GST/creatinine ratio, pi-GST/creatinine ratio, sNGAL, and uNGAL/creatinine ratio concerning the histopathologic examination, the duration of the disease, and number of relapses did not show any significant differences. Conclusions: 1. Both children with SDNS and those with SRNS were characterized by increased tubular injury marker levels. 2. Patients with SRNS and higher proteinuria are more susceptible to early kidney damage.